Development of PEBAX Based Membrane for Gas Separation: A Review - Sunarti, Abd Rahman; M. S., Abdul Wahab (Cosmos Scholars Publishing House, 2015)
Polymer is among the favorite materials used for membrane separation as they are cheap, easily cast, low maintenance cost and commercially easy to get eventhough the material needs to be altered to meet the separation industry specific needs. There are two common issues in membrane preparation which are the produced sheet are too brittle and has no strength to withstand pressure during separation process and the porosity of the sheet sometimes not suitable with the gas kinetic diameter for the separation to occur. PEBAX or Poly ether block amide is the answer for the issues as this elastomer provides good mechanical strength from the hard segment of the crystalline poly amide block while the soft polyether will drive the separation process. This unique material can be casted either by phase inversion of the PEBAX itself with other polymer or by coating them on the other polymer substrate.